Moral Realism and Faultless Disagreement. (21st April 2015) - Cohnitz, Daniel
Abstract: Is moral realism compatible with the existence of moral disagreements? Since moral realism requires that if two persons are in disagreement over some moral question (that has a determinate answer) at least one must be objectively mistaken, it seems difficult to uphold that there can be moral disagreements without fault. Alison Hills argued that moral realism can accommodate such disagreements. Her strategy is to argue that moral reasoners can be faultless in making an objectively false moral judgement if they followed the relevant epistemic norm, i.e. follow your conscience, when making their judgement. I will argue that Hills' strategy does not work. The putative epistemic norm follow your conscience does not trump moral truth, because believing something wrong for the wrong reasons is worse than believing something right for the wrong reasons.1